Masa Depan E-Business Di Indonesia (Studi Kasus : PT. Gojek Indonesia) - Ridho Fachrozie; Ghilman Rozy Hrp; Nurbaiti Nurbaiti (LPPM Universitas Labuhanbatu, 2021)
The Internet thAt is growing day by day has a significant impact in all fields, both in the world of education and also in the business world. with the internet, it can change business patterns from traditional or conventional businesses to electronic technology businesses or e-business. gojek is one example of the application of electronic systems into the operations of a business, just by accessing the application, gojek can easily blend into the indonesian market where people depend on it. smartphones. the purpose of doing this research is so that we can find out and analyze the future of e- business in indonesia, especially the future at pt gojek indonesia. the approach taken in this research is to use a qualitative approach by using the literature study method. the data of this research were obtained by collecting writings from several articles, several books and all forms of sources related to the object of research. the results of this study indicate that the future of PT Gojek Indonesia will be bright because they continue to innovate to remain competitive in the future.